2015
DOI: 10.1371/journal.pone.0127331
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dielectric Properties of Ferrite-Dielectric Based Metamaterial

Abstract: A ferrite-dielectric metamaterial composed of dielectric and ferrite cuboids has been investigated by experiments and simulations. By interacting with the electromagnetic wave, the Mie resonance can take place in the dielectric cuboids and the ferromagnetic precession will appear in the ferrite cuboids. The magnetic field distributions show the electric Mie resonance of the dielectric cuboids can be influenced by the ferromagnetic precession of ferrite cuboids when a certain magnetic field is applied. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Magnesium is another tunable material that can undergo metal-to-dielectric phase-transition to form magnesium hydride (MgH 2 ) by absorbing up to 7.6 wt % hydrogen 280 , which has been used in tunable metamaterials [281][282][283] . Last but not least, ferrites (magnet) materials are used specifically by coupling of the ferrite cuboid with Mie resonance of dielectric materials to magnetically tune the properties of different types of the metamaterials [284][285][286][287][288][289] .…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium is another tunable material that can undergo metal-to-dielectric phase-transition to form magnesium hydride (MgH 2 ) by absorbing up to 7.6 wt % hydrogen 280 , which has been used in tunable metamaterials [281][282][283] . Last but not least, ferrites (magnet) materials are used specifically by coupling of the ferrite cuboid with Mie resonance of dielectric materials to magnetically tune the properties of different types of the metamaterials [284][285][286][287][288][289] .…”
Section: Resultsmentioning
confidence: 99%
“…The significant progress in information technology, electronics and wireless communication devices together with a new trend of miniaturization and Progress, Challenges and Opportunities in Divalent Transition Metal-Doped Cobalt Ferrites… DOI: http://dx.doi.org/10.5772/intechopen.93298 multifunctionality led to the necessity of new materials with special characteristics. Considering the structural, electric and magnetic properties, the nanosized ferrites may become important candidates for applications in microwave communication systems, electromagnetic devices, resonators and filters for satellites, broadcasting equipment, batteries, supercapacitors and many other microwave devices [70].…”
Section: Applications Of Dielectric Propertiesmentioning
confidence: 99%
“…In 2006, Linden et al proposed a 1D MFPC that can be utilized in the visible spectrum and affirmed the transfer features of the MFPC by experimentation [9]. In recent years, Bi et al took research in metamaterials based on ferrite dielectrics and found that the dielectric characteristics of the metamaterial can be modulated by changing the magnetic field in the ferrite [10]. Significant progress has been made with these researches and the ferrite materials have become widely used to satisfy the need for adjustability.…”
Section: Introductionmentioning
confidence: 99%